Tricky design the ethics of things - Fisher, Tom 1958-; Gamman, Lorraine (Bloomsbury Visual Arts, 2019)
"Tricky Things responds to the burgeoning of scholarly interest in the cultural meanings of objects, by addressing the moral complexity of certain designed objects and systems. The volume brings together leading international designers, scholars and critics to explore some of the ways in which the practice of design and its outcomes can have a dark side, even when the intention is to design for the public good. Considering a range of designed objects and relationships, including guns, eyewear, assisted suicide kits, anti-rape devices, passports and prisons, the contributors offer a view of design as both progressive and problematic, able to propose new material and human relationships, yet also constrained by social norms and ideology. This contradictory, tricky quality of design is explored in the editors' introduction, which positions the objects, systems, services and 'things' discussed in the book in relation to the idea of the trickster that occurs in anthropological literature, as well as in classical thought, discussing design interventions that have positive and negative ethical consequences"--Page 4 of cover
Keywords: Industriedesign; Sachkultur; Ethik; Industrial design / Moral and ethical aspects; Design / Moral and ethical aspects; Material culture; Aufsatzsammlung